Gog and Magog (Yakjuj wa Makjuj) Stories in Sundanese Manuscripts - Faiz Karim Fatkhullah; Tajudin Nur; I. Syarief Hidayat; Undang Ahmad Darsa (IAIN MADURA, 2019)
Gog and Magog will appear in the end of the world as a sign of doom. Their mysterious figure, making the story Gog and Magog interesting as well as a debate among experts. This study aims to reveal the reception of the Sundanese to the story of Gog and Magog which is represented by three Sundanese texts: Saifu Ad-Dharīb (SaD), Lajaj Dajal (LD), and Nawādirul 'Ulūm (NU). This study used a descriptive qualitative method with the reception theory approach. Of the three manuscripts, there are a diversity reception informing the advantages and disadvantages of each manuscript. The reception of who is Magog, LD's text calls them communist descendants. Regarding its existence, the SaD manuscripts say they are on Mount Qaf. Related to their numbers, the three manuscripts mention the numbers very much; SaD mentioned they have 400,000 troops, and each of them gave birth to 1000 offspring. NU's manuscripts reveal all objects will be destroyed and humans will become their prey. SaD's manuscripts mention their deaths due to massive winds; LD manuscripts say they died from being attacked by thousands of mosquitoes, while NU manuscripts say they died of disease.